Rola prokuratora w postępowaniu przygotowawczym przed międzynarodowymi trybunałami karnymi: [The role of prosecutor in pre-trial before International Criminal Tribunals] (Studia Prawnicze / The Legal Studies, 2010)
Pozycja prokuratora w postępowaniu przed trybunałami międzynarodowymi zależy w dużej mierze od tego, jaką pozycję posiada sam trybunał w świetle prawa międzynarodowego. Różne sposoby organizacji i funkcjonowania tych trybunałów są przede wszystkim rezultatem odmiennych sposobów rozwiązywania sytuacji post-konfliktowych w konkretnym przypadku. Jednak podstawowym czynnikiem wpływającym na rolę, jaką odgrywa prokurator międzynarodowego trybunału karnego, jest ukształtowanie postępowania przed takim trybunałem. Twórcy trybunałów musieli za każdym razem utworzyć nowy wzorzec postępowania. Procedura ta nie powiela żadnej z procedur krajowych, stanowiąc za każdym razem twór sui generis. Opiera się na elementach znanych z różnych systemów krajowych, nie zawsze ze sobą kompatybilnych. Już w pierwszych orzeczeniach Międzynarodowego Trybunału Karnego do spraw Jugosławii (MTKJ) wyjaśniono, że postępowanie przed trybunałami międzynarodowymi stanowi jedyny w swoim rodzaju amalgamat elementów systemu common law i prawa kontynentalnego, który nie naśladuje jednak ściśle zasad charakterystycznych dla jednego z nich. Różnice między systemami common law i prawa kontynentalnego stały się zresztą przyczyną nieporozumień i długich negocjacji już w momencie tworzenia pierwszych międzynarodowych trybunałów wojskowych w Norymberdze i Tokio. Obecnie nie ulega wątpliwości, że funkcjonowanie międzynarodowych trybunałów karnych stało się forum zbliżania różnych systemów postępowania karnego prowadząc do powstania nowej jakości w sferze postępowania karnego. W wyniku wielu lat działania trybunałów ad hoc, jak również trybunałów quasi-międzynarodowych, można obecnie mówić o wytworzeniu się pewnych wzorców, wspólnych cech i rozwiązań. In the process of creation of international criminal tribunals not only criminal procedure sui generis was designed but also for the first time detailed powers of prosecutor had to be adapted to specificity of their functioning. Procedure of international criminal tribunals creates new foundations to the position of prosecutor. The role that is played by this organ in international justice system depends mainly on the position of the tribunal itself. The creators of international tribunals applied legal instruments from several legal systems choosing solutions that seemed most appropriate for organs of international justice. In the consequence such procedure constitutes an amalgamate of common law institutions and solutions used in continental legal systems. In the negotiations during creation of the International Criminal Court for many years the best solutions were discussed and designed. Several questions regarding the shape of procedure had to be answered. The answers influenced not only the powers of prosecutor but also the role of tribunal. The place of prosecutor as an organ of the tribunal was the first issue of fundamental importance. International military tribunals in Nuremberg and Tokyo did not create prosecutor as an independent organ. Prosecutors acted only in the name of the victorious governments. It was only with creation of ad hoc tribunals – International Criminal Tribunal for former Yugoslavia and International Criminal Tribunal for Rwanda – that prosecutor became an independent organ, equipped with his own powers. At the time being, in the procedure before the International Criminal Court independence of prosecutor is the fundamental element of his status and is protected equally to independence of judges. Secondly, the choice between opportunity and legality of prosecution had to be made. It was agreed that prosecutor should take actions only in the most severe situations regarding most serious violations of international criminal law when specific circumstances indicate that they are in the interest of an international organ of justice. Perpetrators of international crimes are usually too numerous to be brought to justice before an international organ. In such situation it is accepted that prosecutor should initiate criminal proceedings only when he sees the procedure to be in interests of international justice. The issue of initiation of procedure was equally crucial. Each tribunal offers to prosecutor such powers, although in the ICC it was one of the most disputed solutions. In the consequence prosecutor plays an important role in the functioning of international justice. Not only he can initiate procedure proprio motu but also chooses situations and perpetrators that should be brought to justice before international tribunals. The shape of pre-trial stage constitutes an amalgamate of different criminal justice systems – both elements of common law and continental legal systems have been employed in order to create procedure most fitted to the specificity of situations that have to be dealt with by international tribunals. Such institutions as disclosure of charges and documents come from common law. Continental legal systems provided solutions of confirmation of indictment and active role of Pre-Trial Chamber in the pre-trial stage. In the consequence system of checks and balances was created – prosecutor conducts the pre-trial stage but most important decisions have to be confirmed by a judicial organ. This article presents powers of prosecutors of international criminal tribunals during the pre-trial stage of proceedings. It focuses on such institutions as power to initiate of proceedings and its limitations, preliminary examination of a case, authorization of investigation, conditions of such authorization and powers of prosecutor to act on a territory of states. Many procedural issues concerning the role of prosecutor have been explained during the judicial activities of ad hoc tribunals. It can be expected that in the jurisprudence of the ICC problems concerning the role of prosecutor of international tribunal will be further developed.